1973
DOI: 10.1139/v73-346
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Proton Nuclear Magnetic Resonance Spectra of Aryl and Mono- and Disubstituted N-Methylazoles

Abstract: Proton n.m.r. spectra of 111 substituted azoles are compared. The influence of the azole ring on the chemical shifts of substituent phenyl protons is discussed. A correlation between N-methyl chemical shifts and the structural characteristics of the N-methyl group in mono- and disubstituted azoles is noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Oxazolylbenzaldehyde 4aa was synthesized from methyl 4-formylbenzoate (33) by treatment with tosylmethyl isocyanide (TosMIC) to construct the oxazole ring, followed by transformation of the ester function to aldehyde (Scheme 11).…”
Section: Chemistrymentioning
confidence: 99%
“…Oxazolylbenzaldehyde 4aa was synthesized from methyl 4-formylbenzoate (33) by treatment with tosylmethyl isocyanide (TosMIC) to construct the oxazole ring, followed by transformation of the ester function to aldehyde (Scheme 11).…”
Section: Chemistrymentioning
confidence: 99%
“…We interpreted the features of the 'H nmr spectra assignable to entities present in the uncyclised aminopyrazole (that is, substituents or protons at positions 1, 2, and 3) by direct comparison with the aminopyrazoles, and by general resemblances to other 1-and 1,3-substituted pyrazoles (13)(14)(15)(16); the proton signals from the 4-methyl-, 5-methine-, and 6-melhylene functions were simply assignable by proton count and by signal multiplicity.…”
Section: ) Than Anisotropic Influencesmentioning
confidence: 99%
“…Proton nlnr alkyl shifts have proved useful for compounds [9][10][11][12] we have now found that the distinguishing between N-alkyl isomers in the correlation previously noted (1) is reversed due azole series due to increased shielding of the to the anisotropic effects of the 5-hydrazono alkyl group in the structural units (1) substituent a t the 1-N-alkyl site. As far as we are However, these trends may break down when substituents containing special anisotropic effects are present.…”
mentioning
confidence: 95%